Prevalence and severity of bacterial blight and anthracnose diseases of cassava in different agroecological zones of Nigeria - Onyeka, T.J.; Owolade, O.F.; Ogunjobi, A.A.; Dixon, Alfred G.O.; Okechukwu, R.U.; Bamkefa, B. (2008)
Geo-referenced surveys were conducted in 2001 and 2003 to assess the prevalence and severity of cassava bacterial blight (CBB) and cassava anthracnose disease (CAD) in different agro-ecological zones of Nigeria. A total of 132 fields were visited in 2001 as follow: humid forest (HF) 42, derived savannah (DS) 38, southern guinea savannah (SGS) 16, northern guinea savannah (NGS) 16 and Sudan savannah (SS) 20. In 2003, 277 fields were visited: HF (83), DS (143), SGS (22), NGS (11), and SS (18). CBB prevalence was greater than 70% in all ecozones in 2001; 33.7% in HF, 65.7% in DS and greater than 90% in others in 2003. CAD prevalence was greater than 90% in HF for the two surveys, 44.7% and 61.5% for 2001 and 2003 respectively in DS, while it was not observed in the other zones. In both surveys, more than 80% of CBB infected fields in all ecozones were moderately severe, except in SS where 47% of fields in 2003 were highly severe. In both HF and DS, more than 30% of fields in 2001, and less than 20% in 2003, had highly severe CAD symptoms. Prevalence of CBB was negatively correlated with annual precipitation and positively correlated with maximum temperature of the ecozones, while prevalence of CAD had strong positive relationship with the annual precipitation and negative association with maximum temperature. The distribution patterns of the diseases found in this study provide a baseline for disease management programme in the rapidly expanding cassava industry in Nigeria, and implications of the results for cassava industry were discussed.